CARRYING OUT OF WORK ON CERTIFICATION OF PRODUCTION AT RUP «BMZ» - E. G. Polozova; Ju. V. Dvornik (Литьë и металлургия)
One of the terms of the product market expansion is production on its compliance with the requirements of standards and norms of those countries?  where the works supplies its production. The certificates received for production of RUP «BMZ» are given.